Financial Management for Small Businesses Financial Statements & Present Value Models - Robinson, Lindon J.; Hanson, Steven D.; Black, J. Roy (Open textbook library., 2020)
This book is for those whose financial management focus is on small businesses. For you, we adapt the traditional financial management themes emphasized in corporate financial management courses to meet the needs of small businesses. Many financial managers of small businesses come from farms or agribusinesses. Others are interested in working for or starting businesses in the food or retail sectors. In most cases, these businesses aren’t organized as C-corporations impacting things like taxes, depreciation, and legal requirements around compiling and reporting financial data. They are rarely publicly traded which creates unique constraints to raising debt and equity capital and calculating required risk-adjusted returns.